Revision of the most important scientific works on the genetic and epigenetic pathways to obesity - Di Vico, Augusto; Liguori, Stefano; Silli, Laura; Rughini, Susanna; Liguori, Aldo (Progress in Nutrition, 2014)
Following a long debate, during last 20 years, regarding the genetics field of human common traits, we can underline the presence of a wide expression of gene variability, adding a large environment influence, we’ll keep the concept that genes will hold our species traits unaltered during the millennia. Although, obesity is the result of an interaction between genetic factors and individual environment. The genetic contribution to interindividual variation in common obesity has been estimated at 40-70%. Yet despite a relatively high heritability, the search for obesity susceptibility genes has been an arduous task. The goal of this review is to check the published works on this matter (genetics and epigenetics influence on gene expression) and underline that according to the recent evident bases the genes associated with risk of obesity are susceptible to epigenetic mutations; the epigenetic markers influence the expression of genes associated with obesity.